Development of the human perihypoglossal nuclei from mid-gestation to the perinatal period: A morphological study. (21st June 2022) - Yamaguchi, Katsuyuki; Yazawa, Takuya
Highlights: Four perihypoglossal nuclei (PHN) were identified at mid-gestation. Topographic relationships among the four nuclei were conserved until perinatal period. Dorsal PHN was composed of the intercalated nucleus and prepositus nucleus. Ventral PHN was composed of the nucleus of Roller and interfascicular nucleus. Neuronal cytoarchitecture of each PHN matured rapidly by 28–30 postmenstrual weeks. Abstract: Introduction: Morphological data on the development of the human perihypoglossal nuclei (PHN) are scarce. This study describes the morphology of the human PHN from mid-gestation to the perinatal period. Materials and methods: Ten brains were collected from infants aged 21–43 postmenstrual weeks (PW). Serial sections were cut and stained using the Klüver–Barrera method. Morphometric parameters [volume, neuronal numerical density (Nv) and total number (Nt), and neuronal profile area (PA)] were analyzed from microscopic observations. Results: Four PHN [nucleus of Roller (RO), interfascicular nucleus (IF), intercalated nucleus (IC), and prepositus nucleus (PR)] were identified at 21 PW. Medium-sized to large, oval, or polygonal neurons were concentrated in the ventral nuclei (RO and IF) and localized regions near the IC–PR transition of the dorsal nuclei (IC and PR). Small to large neurons of various shapes were scattered across the dorsal nuclei. The PR showed rostrocaudal differences in the neuronal cytoarchitecture. The volume of each nucleus increased between 21 and 43 PW, with a typical exponential increase for the dorsal nuclei. The Nv in each nucleus exponentially decreased, whereas the Nt was almost stable. The median PA linearly increased for every nucleus, and the increasing rates were greater for the ventral nuclei than those for the dorsal nuclei. Conclusions: The dorsal and ventral PHN are identifiable at mid-gestation. The topographic relationships of the four nuclei are conserved until the perinatal period. The characteristic neuronal cytoarchitecture of each group is rapidly formed by 28–30 PW.